Persepsi Mahasiswa/I PMI Kelas 3B terhadap Podcast Close the Door Deddy Corbuzier pada Kampanye Pilkada DKI Jakarta 2024 di Youtube - Azzahra, Dinda Putri; Marwazy, Akhmad; .F, Muhammad Khadafi Suhaemi; Fadilah, Fatimah Zahro; Nisa, Pia Khoirotun (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the role of Deddy Corbuzier's podcast on the perception of PMI 3B students on the 2024 DKI Jakarta gubernatorial election campaign on YouTube and to analyze the forms of the role of Deddy Corbuzier's podcast on the 2024 DKI Jakarta gubernatorial election campaign on YouTube on the perception of PMI 3B students. This research methodology uses a constructivist paradigm to understand how influencers, through social interaction and digital communication, shape public perception and influence the media economy and political advertising. The approach used is descriptive qualitative. Based on this study, it is concluded that, the perception of PMI class 3B students towards the Close The Door podcast shows that this podcast is effective as a political communication tool for the younger generation. With a relaxed and in-depth format, this podcast makes it easy for students to access political information, in accordance with Robert G. Picard's media economics theory. Deddy Corbuzier's open discussion style and use of YouTube as a distribution platform allow for wide reach at low cost, influencing public perception without large costs. This podcast also functions as a tool that increases political awareness by providing a platform for dialogue, enriching students' political understanding through diverse views. Overall, Close The Door optimizes the attention economy and plays an important role in political campaigns effectively.